2020
DOI: 10.21438/rbgas(2020)071501
|View full text |Cite
|
Sign up to set email alerts
|

Análise do custo e do potencial de geração de energia fotovoltaica em uma universidade pública brasileira

Abstract: Palavras-chave:Energia limpa e renovável; Fotovoltaico; Sustentabilidade; Análise de agrupamentos.Abstract. Cost and potential analysis of photovoltaic power generation at a Brazilian public university. Clean and renewable energy sources, such as solar energy, have stood out for their potential. So, the aim of this work is to estimate the cost and potential of photovoltaic power generation on São Paulo State University (UNESP) campuses. The statistical technique of cluster analysis associated with the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…The values presented in Table 2 summarize the acquisition cost of R$1,051.73 for the conventional energy system and of R$1,389.80 for the photovoltaic energy system based on retail prices in the domestic market. An aggravating point in the use of solar energy is the fact that the costs of implementing photovoltaic systems are still very expensive (Silva et al, 2020). However, according to Souza and Penha (2020), when studying cash flow projection they observed that the investment in a photovoltaic energy system with a life expectancy of up to 25 years proved to be attractive when verifying the payback time of the investment from the fifth year of use.…”
Section: Resultsmentioning
confidence: 99%
“…The values presented in Table 2 summarize the acquisition cost of R$1,051.73 for the conventional energy system and of R$1,389.80 for the photovoltaic energy system based on retail prices in the domestic market. An aggravating point in the use of solar energy is the fact that the costs of implementing photovoltaic systems are still very expensive (Silva et al, 2020). However, according to Souza and Penha (2020), when studying cash flow projection they observed that the investment in a photovoltaic energy system with a life expectancy of up to 25 years proved to be attractive when verifying the payback time of the investment from the fifth year of use.…”
Section: Resultsmentioning
confidence: 99%
“…Mesmo sendo considerada energia limpa e renovável, a geração hidroelétrica pode causar grandes problemas ambientais, sociais e culturais, como alagamentos, perda de biodiversidade, desapropriação de áreas indígenas, comunidades ribeirinhas, perda da identidade cultural, etc. Todos esses aspectos inviabilizam mais ainda o uso desse tipo de energia e impulsiona cada vez mais a utilização de outras fontes energéticas (SILVA et al, 2020).…”
Section: Introductionunclassified